The Effects of Smartphone on Students’ Learning at National Dong Hwa University - Sianturi, Murni; A, Nurhayati (Journal of Education and Vocational Research, 2019)
This study aimed to examine whether students consider that their mobile phones are useful devices for academic learning. Moreover, it was to investigate whether students’ opinion on their mobile devices are useful devices for academic learning have any differences based on students’ gender, age, college and type of their mobile phone; and students’ opinion regarding capabilities of all features of Smartphone have positive correlation for effect of Smartphone to students’ learning. The participants were students of four colleges in National Dong Hwa University. The effectiveness of Smartphone was measured by questionnaire consisted students’ opinion on using their Smartphone in learning. Based on the findings of this study, students consider that their mobile phones were useful devices for academic learning, and provided positive impact in students’ learning. However, students considered that their mobile phones were useful devices for academic learning did not depend on their gender, age, college, or type of their Smartphone. Capabilities of all features of Smartphone had positive correlation for effect of Smartphone to their learning.